(untitled) (MAUSAM, 2024)
The present study has analyzed variability in climate variables annually and seasonally (kharif and rabi season), viz. rainfall and temperature during from 1985 to 2021 and found its their impact on productivity of maize and wheat crops at different seven locations of Himachal Pradesh. The study found that, except for the maximum temperature in the kharif season, practically all of the seven sites had significant increases in maximum and minimum temperatures annually and seasonally over the study period. Highest positive deviation was found in minimum temperature of Kangra district rabi season i.e., 2.12ºC while lowest was found in kharif season i.e., 0.50 ºC. Pettit’s homogeneity test showed climate change year 1998 and afterward annually minimum temperature was significantly rise. Climate change year showing positive change in rainfall that is showing increasing trend after 1998 at all the locations. Increases in maximum temperature had adverse impact on maize crop yield in the kharif season and a positive impact on wheat yield in the rabi season, whereas rainfall had a positive impact on maize and wheat crop yield.